2003
DOI: 10.17221/3818-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

The essential oil content in caraway species (Carum carvi L.)

Abstract: Caraway fruits contain 1-6% of essential oils consisting of about 30 compounds, from which carvone and limonene account form the main portion, about 95%. To evaluate the quality of various caraway cultivars, the amounts of essential oils and the carvone/limonene ratio were measured. The most common method of essential oil evaluation is steam distillation in accordance with Standard ČSN 58 0110, but an alternative method -supercritical fluid extraction (SFE) -was also investigated in this paper. Ground caraway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 8 publications
2
31
0
3
Order By: Relevance
“…In our experiment, the main components were carvone and limonene, whose mixture constituted from 97.69 to 98.62% of total oil composition. According to other researchers (Kallio et al 1994;Ahroet al 2001;Sedláková et al 2003a;Seidler-Lozykowska et al 2010), the percentage of carvone and limonene in essential oil ranges from 93.2 to 99.8%. Apart from monoterpenes, the essential oil contains sesquiterpenes (β-bourbonene, β-elemene, trans-caryophyllene, trans-muurola-4(14), 5-diene and caryophyllene oxide).…”
Section: Essential Oil Constituentsmentioning
confidence: 91%
See 3 more Smart Citations
“…In our experiment, the main components were carvone and limonene, whose mixture constituted from 97.69 to 98.62% of total oil composition. According to other researchers (Kallio et al 1994;Ahroet al 2001;Sedláková et al 2003a;Seidler-Lozykowska et al 2010), the percentage of carvone and limonene in essential oil ranges from 93.2 to 99.8%. Apart from monoterpenes, the essential oil contains sesquiterpenes (β-bourbonene, β-elemene, trans-caryophyllene, trans-muurola-4(14), 5-diene and caryophyllene oxide).…”
Section: Essential Oil Constituentsmentioning
confidence: 91%
“…Some authors (Kallio et al 1994;Sedláková et al 2003a;Laribi et al 2010) postulate that there are more components in caraway essential oil.…”
Section: Essential Oil Constituentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carvone had the second highest peak area (2.28×10 7 ) in naturally fermented kvass, but it was not present in dry kvass. According to Sedláková et al (2003), carvone and limonene form the main portion of essential oils in caraway fruits, which are an ingredient in the rye bread used for naturally fermented kvass production. Salim et al (2015) reported that drying affected the reduction of carvone in spearmint.…”
Section: Aroma Volatiles In Naturally Fermented and Dry Kvassmentioning
confidence: 99%